mRNA vaccines induce durable immune memory to SARS-CoV-2 and variants of concern - Goel, Rishi R.; Painter, Mark M.; Apostolidis, Sokratis A.; Mathew, Divij; Meng, Wenzhao; Rosenfeld, Aaron M.; Lundgreen, Kendall A.; Reynaldi, Arnold; Khoury, David S.; Pattekar, Ajinkya; Gouma, Sigrid; Kuri-Cervantes, Leticia; et al. (Science (American Association for the Advancement of Science), 2021)
Vaccination against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has proven highly effective at preventing severe COVID-19. However, the evolution of viral variants, and waning antibody levels over time, raise questions regarding the longevity of vaccine-induced immune protection. Goel et al . examined B and T lymphocyte responses in individuals who received SARS-CoV-2 messenger RNA vaccines. They performed a 6-month longitudinal study of individuals who never had SARS-CoV-2 infection compared with people who had recovered from SARS-CoV-2. Humoral and cellular immune memory was observed in vaccinated individuals, as were functional immune responses against the Alpha (B.1.1.7), Beta (B.1.351), and Delta (B.1.617.2) viral variants. Analysis of T cell activity suggested that robust cellular immune memory may prevent hospitalization by limiting the development of severe disease. —PNK Blood analysis of individuals vaccinated with the Moderna SARS-CoV-2 mRNA vaccine reveals distinct trajectories of immune memory responses. The durability of immune memory after severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) messenger RNA (mRNA) vaccination remains unclear. In this study, we longitudinally profiled vaccine responses in SARS-CoV-2–naïve and –recovered individuals for 6 months after vaccination. Antibodies declined from peak levels but remained detectable in most subjects at 6 months. By contrast, mRNA vaccines generated functional memory B cells that increased from 3 to 6 months postvaccination, with the majority of these cells cross-binding the Alpha, Beta, and Delta variants. mRNA vaccination further induced antigen-specific CD4 + and CD8 + T cells, and early CD4 + T cell responses correlated with long-term humoral immunity. Recall responses to vaccination in individuals with preexisting immunity primarily increased antibody levels without substantially altering antibody decay rates. Together, these findings demonstrate robust cellular immune memory to SARS-CoV-2 and its variants for at least 6 months after mRNA vaccination.